2019
DOI: 10.1021/acs.jpcb.9b00890
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Structure, Hydrogen Bonding, and Proton Conductivity in Half-Neutralized Diamine Ionic Liquids

Abstract: Recent experiments on proton conducting ionic liquids point to half-neutralized diamine-triflate salts as promising candidates for applications in power generation and energy conversion electrochemical devices. Structural and dynamical properties of the simplest among these compounds are investigated by a combination of density functional theory (DFT) and molecular dynamics (MD) simulations based on an empirical force field. Three different cations have been considered, consisting of a pair of amine-ammonium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…In certain PILs, proton transfer can be enhanced by a Grotthuss-like mechanism when a neutral molecule, such as imidazole, is added to the liquid. A similar mechanism has been detected in PILs with partially neutralized diamines . Further insights into the complexity of certain PILs has been obtained by us; we have shown that proton transfer in fully ionized liquids can be mediated by the clustering of like-charge ions (specifically amino acid anions).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In certain PILs, proton transfer can be enhanced by a Grotthuss-like mechanism when a neutral molecule, such as imidazole, is added to the liquid. A similar mechanism has been detected in PILs with partially neutralized diamines . Further insights into the complexity of certain PILs has been obtained by us; we have shown that proton transfer in fully ionized liquids can be mediated by the clustering of like-charge ions (specifically amino acid anions).…”
Section: Introductionsupporting
confidence: 75%
“…A similar mechanism has been detected in PILs with partially neutralized diamines. 18 Further insights into the complexity of certain PILs has been obtained by us; 19−21 we have shown that proton transfer in fully ionized liquids can be mediated by the clustering of like-charge ions (specifically amino acid anions).…”
Section: Introductionmentioning
confidence: 88%
“…Sample Preparation and Simulation Setup. Slabs consisting of 216 [DAEt][Tf] molecules have been prepared starting from a homogeneous liquid sample equilibrated at T = 440 K (see ref 19), increasing the periodicity L z along z in discontinuous steps, while keeping constant the periodicity along xy. At first the change of periodicity has to be slow, and each increase in L z (by ∼1 Å) is followed by minimization of the energy at constant volume, and by brief (50 ps) equilibration at NVT conditions back to 440 K. Soon a density gap forms, separating two adjacent surfaces, and it becomes possible to extend L z by large (∼10 Å) steps without perturbing much the system.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate all these issues, a paradigmatic role could be attributed to a family of PIL compounds made of aliphatic diamine cations and the trifluoromethanesulfonic (triflate) anion, whose chemical physics properties, and proton conductivity in particular, have been investigated by experiments 16 and by simulation. 19 More precisely, cations in these compounds consist of a conjugated pair of amino (−NH 3 + )/ amine (−NH 2 ) terminations, joined by an aliphatic segment [−(CH 2 ) n −], and their charge is compensated by an equal number of triflate (CF 3 SO 3 − , [Tf] − ) anions. In our study we consider the case n = 2, ethylenediamine triflate, [DAEt][Tf], and, to a lesser extent, the case n = 4, butyldiamine triflate, [DABu][Tf].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation